With the greatest respect, I cannot agree…: an investigation into the discourse of dissenting in selected Malaysian judicial opinions - Noraini Ibrahim; Abdul Hadi Awang (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2011)
Modern judicial opinions are by tradition, a reflection of hundreds of years of history and tradition. Judges usually give their decision and order verbally in court, and legally significant and important judgments notably from the higher courts, are then published in law reports and become the substance of common law. ‘Dissent’ is the written expression of a judicial opinion that results in the court not arriving at a unanimous decision. Hence, the dissenting judge will have to state his disagreement by focusing on the issue(s) of law before proceeding to provide an explanation. Literature has shown that dissenting opinions are not a feature of all legal jurisdictions nor are they presented in the same way. This paper aims to discuss the discourse of ‘dissenting’ from an analysis of selected Malaysian judicial opinions. In this respect a mixed-method approach was employed to gather the data, while data analysis and the linguistic features were drawn from Trosborg’s (1997) text typology. The main findings reveal that modality, adverbials as well as context-specific structures alluding to adherence and mutual respect, are employed to temper the emotive tone of the judges. Interestingly however, and contrary to literature, non-adherence to such practice has also been located. The question is, is such a position ideological?